Increasing sustainability in the tomato processing industry: environmental impact analysis and future development scenarios - Eslami, Elham; Abdurrahman, Emadaldin; Pataro, Gianpiero; Ferrari, Giovanna (Frontiers in Sustainable Food Systems, 2024)
The agri-food sector has been identified as one of the most significant contributors to environmental degradation and emissions. Thus, in order to respond to the societal demand for cleaner and greener products, in recent years the food industry has been striving to identify and apply more sustainable practices to minimize the negative impact on the environment. Within the agri-food sector, one of the industries requiring efforts to mitigate its environmental footprint is the tomato processing industry, which represents an important industry within the Italian industrial food processing sector. Efficient utilization of resources and the adoption of innovative methods in the production lines of the tomato processing industry can be envisaged as strategic measures to increase sustainability. This work aims to discuss the results of the case study in which an Italian tomato processing company has been analyzed by applying the LCA methodology.Method: Foreground data were obtained from the tomato processing facility located in Southern Italy, and the Ecoinvent database was the source of background data. The assessment was carried out by SimaPro software using ReCiPe 2016 (V1.03). The feasible conservation strategies in the production line have been evaluated through water-energy nexus simulation by SuperPro Designer®, before the implementation, and the different scenarios to decrease the environmental load have been evaluated by SimaPro.This study demonstrates that the production of 1 kg of peeled tomatoes and tomato puree leads to greenhouse gas emissions of 0.083 kg CO2 eq and 0.135 kg CO2 eq, respectively.A deeper analysis to evaluate the contribution of the different tomato processing stages indicated that the thermal units are the main ones responsible for adverse effects on the environment and any improvement in their performance can be seen as an unmissable opportunity. The conservation strategies identified resulted in considerable water (23.4%), electricity (14.7%), and methane (28.7%) savings, and consequently, in 16% and 19% reduction of global warming potential in peeled tomato and tomato puree production lines, respectively. These findings provide new insights for tomato processing companies wishing to adopt more sustainable processing practices, reducing to a considerable extent their environmental impact and improving their economic performance.